Water and Nitrogen Distribution Uniformity for Different Drip-lengths under Drip Irrigation System - Kumar, Mukesh; Rajput, T. B. S.; Patel, Neelam (Journal of Agricultural Engineering, 2014)
A field experiment was conducted at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi during 2010 to study the effect of different drip-lengths (lateral) (25, 50, 75 and 100 m) and system operating pressures (0.5, 1.0 and 1.5 kg.cm-2) on water and nitrogen distribution uniformity under drip irrigation system. The varying drip lengths and system operating pressures significantly (P